Development of a Google Chrome Browser Extension for Website Security Assessment Based on OWASP Top 10 - รุ่งแจ้ง ธนกฤต; พุ่มจันทร์ วิรัญญา; พ่วงกำเหนิด สุพจน์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research aimed to develop a Google Chrome browser extension for evaluating website security based on the OWASP Top 10 framework, and to assess the performance of the extension by comparing its ability to detect risky websites, as well as to examine user satisfaction. This study was conducted as applied research. The sample consisted of 50 users and 5 experts in information technology and cybersecurity. The research instruments included the developed browser extension, a user questionnaire, and an expert evaluation form. Data were analyzed using mean () and standard deviation (SD). The results showed that (1) the developed extension was able to detect and alert website security risks based on the OWASP Top 10 framework; (2) when comparing its detection capability against predefined criteria, the system demonstrated an appropriate level of performance; and (3) users reported a high level of overall satisfaction (x̄= 4.18, SD = 0.47), while experts rated the system at a high level of appropriateness (x̄= 4.42, SD = 0.38). These findings indicate that the system is suitable for practical use. However, this evaluation focused on user perception and did not cover in-depth technical vulnerability testing.